Digitalization and Inclusive Education: Common Ground - D. Z. Akhmetova; T. S. Artyukhina; M. R. Bikbayeva; I. A. Sakhnova; M. A. Suchkov; E. A. Zaytseva (Высшее образование в России)
The article addresses the issues related to digitalization in education and in this context – using of its achievements in the inclusive education.The authors analyze the implementation of digital technologies in the educational system, the benefits and risks of digitalization. The most important advantage of digitalization is its applicability in the system of inclusive education. The common ground between the inclusive approach and the use of digital technologies in the education of people with disabilities is studied. Digitalization in the modern world also influences on the civic engagement. In addition, digital citizenship makes it possible to develop professional competencies, ethical standards of culture among the young generation, in particular, among people with disabilities.In this article, the authors study the development of psychological, pedagogical, and communicative competencies of pedagogues required in inclusive education. The approaches to the organization of advanced training for teachers in professional educational institutions are shown.Digital educational technologies have undoubted benefits. If these technologies are used correctly in educational activities, they can help pedagogues to exempt from routine work, and to facilitate the fulfillment of educational tasks for children with disabilities. In order to do this, the entire process of digitalization and the use of artificial intelligence must be mastered. The main thing is to remember that “person” should be in the center of attention during the process of digitalization of socio-political processes.